Quantitative electroencephalogram (qEEG) in combat veterans with post-traumatic stress disorder (PTSD) - Jokić-Begić, Nataša (Array, 2003)
Only a small number of studies have used quantitative electroencephalography (qEEG) in research of the post-traumatic stress disorder (PTSD). The results are not consistent. The aim of the present investigation was to compare qEEG in combat veterans with and without PTSD. The hypothesis is that differences among qEEG characteristics will be found regarding the presence/absence of PTSD. Seventy-nine combat veterans with PTSD comprised the experimental group and 37 veterans without PTSD were included as controls. After the informed consent, they were investigated by the resting EEG recordings. The results demonstrate that PTSD veterans had decreased alpha power and increased beta power. These results suggest an altered neurobiology in PTSD. Various explanations have been offered for alpha activity decrease observed in PTSD veterans. Increased beta rhythm may play a role as a potential marker in differentiating subtypes of PTSD.